The Dominant Influence of Islamic Law in Addressing the Challenges of Upholding the Rights of Rohingya Refugees - Darnela, Lindra; Azmi, Faisal Syafri; Sugitanata, Arif (De Jure: Jurnal Hukum dan Syari'ah, 2025)
The phenomenon of Rohingya refugees in Aceh, Indonesia, presents complex challenges in refugee management, particularly amid regulatory limitations and evolving social dynamics. Based on this context, this study aims to elucidate the dominant role of Islamic law understanding in Aceh in addressing the Rohingya refugee issue, employing Michael Mann's theory of power networks as an analytical framework. This research employs a qualitative, descriptive-analytical approach involving in-depth interviews with 15 informants, including UNHCR staff, activists, local communities, and refugees. Secondary data were obtained from literature and policies on refugee management in Indonesia. The findings indicate that the Acehnese community's understanding of Islamic law, as reflected in ukhuwah Islamiyah and local values such as peumulia jamee, serves as a key factor in accepting refugees. The principle of ukhuwah Islamiyah, rooted in the Qur'an, Hadith and the objectives of Sharia (Maqāṣid al-Sharīʿah), provides the moral and legal foundation for supporting international solidarity. However, challenges arise in social tensions, negative media coverage, and suboptimal implementation of Presidential Regulation No. 125 of 2016 concerning the Handling of Refugees from Abroad. From the perspective of power network theory, this study finds that the ideological network based on Islamic legal values dominates community solidarity. Meanwhile, economic, political, and military networks struggle to balance resource distribution and harmonising local and international policies. The scientific contribution of this research lies in its discovery that Islamic and local values dominate other power networks in refugee management in Aceh. The study recommends the formulation of a qanun on refugee management that aligns with local values as a model for similar contexts in other regions